Performance evaluation of gypsum block wireless sensor network system for real time irrigation scheduling. Issue 1 (31st December 2016) - Veeranna, Jatoth; Patel, Neelam; Mishra, A.K.; Varghese, Cini; Sandeep, N.
Abstract: Majority of farmers in India are irrigating their crops without using any irrigation scheduling criteria. Consequently, the application of excess irrigation water causes water logging, wastage of precious water resources, plant diseases, soil salinity as well as the lack of water results into crop water stress. In the present research work an automated Wireless Gypsum Block Sensor Network System (WSN) was developed to automate irrigation scheduling. The developed gypsum blocks sensors were interlinked with Global System for Mobile (GSM) Module with a microcontroller unit. The sensor performed well in the range of 10–19% volumetric moisture content. These sensors were reliable in the range of 30–90 kPa. The sensors highly correlated with coefficient of determination R 2 = 0.93 with slope 0.13 and small relative root mean square error (RRMSE) for given soil moisture potential at depth of 30–45 cm. The microcontroller starts the pump when soil moisture content reaches below the field capacity (FC) and stops when field reaches at FC of a given threshold rage 15–18. The field information is received by the user through mobile via transmitters and receiver using text messages. The system saves the water an average up to 7%.